2002
DOI: 10.1159/000066079
|View full text |Cite
|
Sign up to set email alerts
|

Functional Results in Stapedotomy with and without CO<sub>2</sub> Laser

Abstract: The authors have studied the use of the CO2 laser in performing primary stapedotomy in 451 patients affected by otosclerosis, operated between 1996 and 2000. Footplate perforation was practised with a traditional method, by means of a microdrill, in 169 subjects. A CO2 laser was instead used in other 282 cases; the authors effected the platinotomy with a single spot, repeated if necessary, with the diameter adjusted to the caliber of the prosthesis. This procedure allowed a smooth-edged p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 17 publications
4
35
0
1
Order By: Relevance
“…Inner ear injury due to direct trauma to the footplate via perforator usage or piston application, bacterial labyrinthitis, reparative granuloma, intralabyrinthine hemorrhage, and perilymphatic fistula are the possible causes [4,26] . The incidence of postoperative SNHL was reported to be between 0.2% and 3% in different studies and 1.4% in our study [16,27,28] . Footplate fractures or floating footplate may lead to further mobilization of the footplate into the vestibule.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Inner ear injury due to direct trauma to the footplate via perforator usage or piston application, bacterial labyrinthitis, reparative granuloma, intralabyrinthine hemorrhage, and perilymphatic fistula are the possible causes [4,26] . The incidence of postoperative SNHL was reported to be between 0.2% and 3% in different studies and 1.4% in our study [16,27,28] . Footplate fractures or floating footplate may lead to further mobilization of the footplate into the vestibule.…”
Section: Discussionsupporting
confidence: 49%
“…In another study, Malafronte et al [15] found ABG≤10 dB in 92% of patients who underwent CO 2 laser stapedotomy and 90% of patients who underwent drill stapedotomy. In a study by Motta and Moscillo, there was a significantly higher rate of successful ABG closure with CO 2 laser compared with microdrill [16] . A recent review comparing hearing outcomes between laser versus non-laser stapedotomy pointed out that laser surgery had significantly better results [5] .…”
Section: Discussionmentioning
confidence: 93%
“…Articles published in Chinese were excluded . After selection based on title and abstract, and subsequent full‐text screening, 21 articles were initially considered eligible for answering our question. Cross‐reference checking revealed no additional articles.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing all 21 studies, it was unclear whether all patients had undergone primary stapes surgery in three studies, more than one type of laser was used without performing subgroup analyses in one study, and air‐bone gap closure was not reported in six studies . In eight studies, the risk of bias was moderate, whereas it was high in the other 13. Adequate randomization, treatment allocation, and blinding were either not achieved or no information was provided regarding these criteria in any of the 21 included studies.…”
Section: Resultsmentioning
confidence: 99%
“…3 Since then, various lasers, such as the Argon, 4-7 the CO 2 ͑Refs. 19,20,31 However, even with a great number of pitfalls, laser surgery of the stapes footplate has been proven to be beneficial in terms of hearing outcome compared to mechanical drilling 11,32 in primary surgery and even more in revision surgery, as the diseased ear is even more vulnerable to mechanical stress induced by conventional surgery. 7 and 13-18͒, and the Erbium:YAG ͑Refs.…”
Section: Introductionmentioning
confidence: 99%